Climate and health benefits of increasing renewable energy deployment in the United States *Strategic deployment of #wind and #solar can maximize carbon reductions and health gains. (29th October 2019) - Buonocore, Jonathan J; Hughes, Ethan J; Michanowicz, Drew R; Heo, Jinhyok; Allen, Joseph G; Williams, Augusta
Abstract: The type, size, and location of renewable energy (RE) deployment dramatically affects benefits to climate and health. Here, we develop a ten-region model to assess the magnitude of health and climate benefits across the US We then use this model to assess the benefits of deploying varying capacities of wind, utility-scale solar photovoltaics (PV), and rooftop solar PV in different regions in the US—a total of 284 different scenarios. Total benefits ranged from 2.2 trillion for 3000 MW of wind in the Upper Midwest to 4.2 million for 100 MW of wind in California. Total benefits and highest cost effectiveness for CO2 reduction were generally highest for RE deployment in the Upper Midwest and Great Lakes and Mid-Atlantic US and lowest in California. Health was a substantial portion of total benefits in nearly all regions of the US Benefits were sensitive to methane leakage throughout the gas supply chain.